AKSESIBILITAS MENUJU FASILITAS KESEHATAN DI KOTA BANDUNG - Prayoga Luthfil Hadi; Tri Basuki Joewono; Wimpy Santosa (Jurnal Transportasi, 2013)
Accessibility influences people’s chance to reach health facilities. The purposes of this study are to analyze the accessibility to reach health facilities and to compare the accessibility for different classes of health facilities in Bandung. Data regarding actual road distance to reach health facilities and the publicly available digital map are processed using ArcGis software. Analysis in this study applies ARIA method. Results show that class C hospital has the highest accessibility and class D hospital has the best distribution than other classes. The analysis also shows that there is significant difference among distributions area according to hospital classes, but there is no significant difference among distributions area according to accessibility classes. These study results in the form of accessibility map to reach hospital can be employed as a base to develop transportation development and accessibility improvement to health services in Bandung.